A Web-based Geographic Information System for Aceh Natural Hazards - Nasaruddin Nasaruddin; Khairul Munadi; M. Dirhamsyah M. Dirhamsyah; Dedi Yuliansyah (Universitas Ahmad Dahlan, 2011)
Aceh province is the most affected area by the tsunami of 26 December 2004. Aceh also has experiencing a number of natural hazards; flood, earthquakes, and volcano’s eruptions. Until now, Aceh has no natural hazards information system which can be used to increase public awareness in order to reduce the impact of the hazards. Natural hazards information system provides hazard maps as the guideline for disaster risk mitigation planning. Therefore, the development of a Web GIS based information system for Aceh natural hazards, referred as Aceh Natural Hazards Information System (ANHIS), is a very strategic decision to increase public awareness of the risks of natural disaster hazard in Aceh. This paper proposes conceptual design and the development of prototype for ANHIS. The main purpose of ANHIS is to visualize many natural hazards maps and disseminate information of the hazardous areas for disaster agencies, researchers and communities in order to help them act on warning issue. In order to develop the prototype, the system requirements, configuration, system design and implementation are presented in this paper. Furthermore, the results of prototype for ANHIS are demonstrated in terms of individual hazard map and multi-hazard map of many natural hazards in Aceh. Finally, the conclusions give the perspectives for future implementation of ANHIS.